A Case of Atrioventricular Block Potentially Associated with Right Coronary Artery Lesion and Ticagrelor Therapy Mediated by the Increasing Adenosine Plasma Concentration - Xiaoye Li; Ying Xue; Hongyi Wu (Case Reports in Vascular Medicine)
Purpose. To report a case of atrioventricular block (AVB) which might be associated with the right coronary artery lesion and the novel oral antithrombotic drug ticagrelor mediated by the increasing adenosine plasma concentration (APC). Case Report. A 65-year-old man was given loading dose of ticagrelor (180 mg) before coronary angiography with total thrombotic occlusion of right coronary artery and one stent was implanted. On second day after successful percutaneous coronary intervention, ECG monitoring showed second-degree (Mobitz type I) AVB with prolonged PR interval (299 ms). Hypothesis was drawn that elevated APC levels caused by ticagrelor would be the reason for AVB after excluding combination drugs or underlying disease. APC might be an indicator of this side effect caused by the P2Y12 receptor inhibitors. On fourth day after shifting to clopidogrel, the ECG showed normal sinus rhythm and PR interval depressed to 190 ms and APC dropped from 1.62 umol/L to 0.92 umol/L. The bradycardia and AVB did not occur in the three-month follow-up. Conclusion. It was important to take the ticagrelor induced bradycardia into account particularly with the myocardial infarction of right coronary artery, treated with atrioventricular block drugs after initiating ticagrelor. Also, we should shift ticagrelor to clopidogrel if AVB occurred.